2004
DOI: 10.1037/0894-4105.18.4.729
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Cortical Surface Features in Localization-Related Temporal Lobe Epilepsy.

Abstract: Differences in cortical surface features between healthy controls (n = 48) and patients with temporal lobe epilepsy (n = 46), ages 14-59, were characterized by means of advanced quantitative MRI processing techniques. Cortical surface features of interest included gyral and sulcal curvature, cortical depth, and total cortical surface area. Epilepsy patients and controls differed on measures of gyrification; the abnormalities generalized despite the focal nature of the primary epileptic process. Changes in cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 31 publications
2
43
1
Order By: Relevance
“…Moreover, only half of the patients had mesiotemporal sclerosis. The direction of our findings favoring increased sulco-gyral folding complexity is in agreement with data from another study, 7 although the exact anatomic localization was not provided.…”
Section: Relationship Between Curvature and Clinical Measuressupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, only half of the patients had mesiotemporal sclerosis. The direction of our findings favoring increased sulco-gyral folding complexity is in agreement with data from another study, 7 although the exact anatomic localization was not provided.…”
Section: Relationship Between Curvature and Clinical Measuressupporting
confidence: 90%
“…21 This initial observation has since been extended in a few automated wholebrain studies of cortical complexity, with inconsistent results. [7][8][9] While our present findings appear at odds with the decreased multilobar fractal dimension previously reported, 8 the nonspecific nature of the fractal dimension measurement limits a direct comparison with our method. Another publication reported a nonlocalized trend toward increased folding as assessed by isoperimetric ratio.…”
Section: Relationship Between Curvature and Clinical Measurescontrasting
confidence: 84%
See 1 more Smart Citation
“…Baxendale et al (18) reported poorer global memory scores in patients with extratemporal pathology relative to patients without extratemporal pathology. Finally, Oyegbile et al (19) found an association between increased whole-brain gyrification in patients with TLE and poorer performances on a variety of cognitive measures. These studies all used whole brain or lobar quantitative MRI measures.…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 99%
“…It was recently used to compare gyrification in preterm and full-term children [Kesler et al, 2006]. It has been widely applied to assess gyrification patterns in adults with different neurological disorders including schizophrenia [Kulynych et al, 1997, Vogeley et al, 2000, White et al, 2003, Sallet et al, 2003, Harris et al, 2004, temporal lobe epilepsy [Oyegbile et al, 2004], Williams syndrome [Schmitt et al, 2002], and dyslexia [Casanova et al, 2004].…”
Section: Measures To Quantify Brain Surface Foldingmentioning
confidence: 99%